Evaluation of Antarctic Ozone Profiles derived from OMPS-LP by using Balloon-borne Ozonesondes - Sepulveda, Edgardo; Cordero, Raul R.; Damiani, Alessandro; Feron, Sarah; Pizarro, Jaime; Zamorano Banda, Felix De La Cruz; Kivi, Rigel; Sanchez, Ricardo; Yela, Margarita; Jumelet, Julien; Godoy, Alejandro; Carrasco Cerda, Jorge Fernando; et al. (My University, 2021)
Predicting radiative forcing due to Antarctic stratospheric ozone recovery requires detecting changes in the ozone vertical distribution. In this endeavor, the Limb Profiler of the Ozone Mapping and Profiler Suite (OMPS-LP), aboard the Suomi NPP satellite, has played a key role providing ozone profiles over Antarctica since 2011. Here, we compare ozone profiles derived from OMPS-LP data (version 2.5 algorithm) with balloon-borne ozonesondes launched from 8 Antarctic stations over the period 2012-2020. Comparisons focus on the layer from 12.5 to 27.5 km and include ozone profiles retrieved during the Sudden Stratospheric Warming (SSW) event registered in Spring 2019. We found that, over the period December-January-February-March, the root mean square error (RMSE) tends to be larger (about 20%) in the lower stratosphere (12.5-17.5 km) and smaller (about 10%) within higher layers (17.5-27.5 km). During the ozone hole season (September-October-November), RMSE values rise up to 40% within the layer from 12.5 to 22 km. Nevertheless, relative to balloon-borne measurements, the mean bias error of OMPS-derived Antarctic ozone profiles is generally lower than 0.3 ppmv, regardless of the season.
Keywords: Ozone Depletion; Forcing (mathematics)